Pengaruh Blanket Warmer Terhadap Suhu Tubuh Pasien Intra Sectio Caesarea Sebagai Upaya Pencegahan Terjadinya Hipotermi - Shinta Aprilia; Anis Ardiyanti; Nafisatun Nisa; Rinda Intan Sari (Pusat Riset dan Inovasi Nasional, 2024)
Sectio caesarean is a surgical process involving an incision that is very risky and causes many complications for the human body. One of the complications caused by an intra-cesarean section is hypothermia. Hypothermia is a medical emergency that occurs when the body loses heat faster than it produces warmth. When the body temperature drops, the nervous system and other organs typically cannot function properly, which in turn affects the functioning of many other organs (Dafiani, 2021). This study aimed to determine the effect of a blanket warmer on the body temperature of intra-cesarean section patients to prevent hypothermia. This quantitative study used a quasi-experimental design (pre-test–post-test with a control group design). Data were collected on intra-section cesarean patients. As many as 35 respondents had been given non-pharmacotherapy therapy in the form of a blanket warmer. The results of the analysis showed that most pregnant women were aged 20–35 years in the no-risk group (91.4%), cesarean section with absolute indication (68.6%), and cesarean section duration < 60 minutes (57.1%). The minimum body temperature of 35.7°C before receiving a blanket warmer, and a maximum body temperature of 36.6°C after receiving one. After carrying out statistical tests using the Wilcoxon test, a P-value of 0.000, or ≤ 0.05, was obtained. In conclusion, blanket warmers influence the incidence of intra-cesarean hypothermia at SMC Telogorejo Hospital. Suggestions for further research include developing variables that can disrupt the thermoregulation system, as well as comparing the use of tools other than blanket warmers to prevent hypothermia before surgery.